Stokes correlation to estimate topological charge from the speckle pattern - Sarkar T.; Singh R.K. (My University, 2025)
The orbital angular momentum (OAM) of the vortex or helical beam, connected with the topological charge (TC) of the beam, has been used as an alternative degree of freedom to encode and decode the information in the optical signals. Many detection schemes have been established to determine the TC configurations and decode the information at the receiver end of the encoded information from the transmitter end for the free space. However, when the helical beam is transmitted through the scattering medium, its wavefront is spatially scrambled without any direct information about the incident helical beam. Here, we propose and experimentally demonstrate a new approach to estimate the TC of the helical beam from the non-imaged randomly scattered pattern. The technique utilizes Stokes parameters (SPs) of the random field to evaluate higher-order SPs fluctuation correlation. A complete theoretical model of the technique is presented and verified with numerical simulation and experimental tests. A good agreement is found between the simulation and experimental results. © 2022, The Author(s), under exclusive licence to Springer-Verlag GmbH Germany, part of Springer Nature.